Strategic Training to the Farmers in the Crop Production (Indian Journal of Extension Education, 2010)
Training is one of the important aspects of human resource development. It can bridge the enormous gap between remarkable yield achieved by the scientist and that obtained by the farmer. Considering the above fact in mind, this study was undertaken to find out the training strategy for farmer with respect to crop production. The present investigation was conducted in Vindhyan Plateau of Sagar district. The Sagar district have eleven blocks out of which four development blocks were selected by random sampling techniques, two villages from each selected block from each village 30 respondent were selected using random sampling procedure. Respondents were those who were cultivating soybean, arhar, wheat and chickpea. Thus data was collected from 240 respondents by interview method with the help of well structure and pretested schedule. The frequency and percentage of respondent’s despairing on and off campus training size of training group’s duration. The findings of the present study have several practical implications, mostly in the nature of suggestion to the planner’s trainers and all other official who are concerned with farmers training programme. This will in turn help in raising farmer socio-economics level through higher production.